Edyta Bątkiewicz-Szymanowska, Tytus Działyński (1796–1861) - Małecka, Monika (Biblioteka, 2019)
Recenzja. Edyta Bątkiewicz-Szymanowska, Tytus Działyński (1796–1861), Kórnik: Polska Akademia Nauk Biblioteka Kórnicka 2018, ss. 266, [2]. ISBN 978-83-85213-65-9